Context-Driven Optimization of Intermittent Communication Systems - Desai, Rohan; Patel, Sophia; Kim, Ethan (Journal of Computer Engineering, 2022)
—The context aware adaptive routing protocol is presented for unicast communication in intermittently connected mobile ad hoc networks (MANETs). The selection of the node is done by the Kalman filter prediction theory and it also makes use of utility functions. The context aware adaptive routing is defined by spray and wait technique, but the time consumption in delivering the message is too high and also the resource wastage is more. In this paper, we describe the spray and focus routing scheme for avoiding the existing problems